Identifikasi Tingkat Keterampilan Bermain Sepak Bola PS. Taruna Desa Potu Kecamatan Dompu Kabupaten Dompu Tahun 2018 - Pratama, Sandi Achmad; Budiman, Budiman (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2020)
he level of football playing skills is one aspect of technique that is very influential on the ability of a soccer player in a match. The technical aspects consist of the technique of tilting the ball, passing and holding the ball, heading the ball and shooting towards the goal.This study aims to determine "To what extent are the Skill Levels owned by Taruna Dompu PS players in 2018".Based on the results of data analysis, it was found that from the 25 players who were subjected to the study, it was found that the average score of the players was 57.87 with enough categories, with the following details that included in the good category were 13 people (52%), moderate categories were 7 people (28%), enough categories as many as 4 people (16%), and less categories as much as 1 person (4%).Furthermore, when viewed from the average score for each player, the highest score is a heading with an average score of 4 (four) test items of 68.5, while the lowest score is obtained from passing with an average number of scores of 44.75. So clearly based on the data above the level of football playing skills possessed by PS players. Potu Village Cadet Dompu District Dompu Regency in 2018, is still lacking and uneven.